Práctica basada en la evidencia y su influencia en la calidad del cuidado enfermero, en el servicio de medicina interna del Hospital Alfredo Noboa Montenegro periodo enero-abril 2020. - Escobar Carey, María José (2020)
The research topic "PRACTICE BASED ON EVIDENCE AND ITS INFLUENCE ON THE QUALITY OF NURSING CARE, IN THE INTERNAL MEDICINE SERVICE OF THE ALFREDO NOBOA MONTENEGRO HOSPITAL PERIOD JANUARY-APRIL 2020" was born with the objective of evaluating evidence-based practice and its influence on the quality of nursing care, in the internal medicine service of the Alfredo Noboa Montenegro Hospital, for the development of the project, its analysis was considered technically indispensable, determining that it is an analytical study which seeks to determine the influence of the application or no application of the PBE on nursing care, for which it was required to carry out a bibliographic search that allows knowing all the components of the object of study and determining the focus thereof, establishing as a technique the survey that allows collecting information in the work of field and be able to achieve the proposed objectives, for the retrieval of information se considered 12 nursing professionals and 138 patients from the internal medicine service who collaborated with the application of the survey, where it is determined that although it is true that they know or have heard about PBE, there are gaps in this knowledge by professionals, and in relation to nursing care, patients consider that it is good and that to lead to excellence, aspects such as communication, empathy, provision of information, problem solving, among other statements in the results, must be improved.